1994
DOI: 10.1016/s0022-5223(94)70334-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic circulatory arrest in operations on the thoracic aorta

Abstract: Hypothermic circulatory arrest in operations on the thoracic aorta Determinants of operative mortality and neurologic outcomeThis study was undertaken to determine the factors that influence the final outcome after hypothermic circulatory arrest Between 1985 and 1992 a uniform method of hypothermic circulatory arrest was used in 200 patients as the primary method of cerebral protection during operations on aneurysms of the thoracic aorta. There were 30 hospital deaths (15 %). Age greater than 60 years (relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(29 citation statements)
references
References 19 publications
1
27
0
1
Order By: Relevance
“…Advanced age, HCA duration, atherosclerotic aneurysms, coronary artery disease, and hemodynamic instability have been reported to be risk factors for TND, which was described by Ergin and colleagues as a reflection of subtle brain injury 10‐13 . It was reported that the use of supplemental cerebral perfusion, either RCP or ACP, did not appear to change the incidence of TND 13 …”
Section: Discussionmentioning
confidence: 99%
“…Advanced age, HCA duration, atherosclerotic aneurysms, coronary artery disease, and hemodynamic instability have been reported to be risk factors for TND, which was described by Ergin and colleagues as a reflection of subtle brain injury 10‐13 . It was reported that the use of supplemental cerebral perfusion, either RCP or ACP, did not appear to change the incidence of TND 13 …”
Section: Discussionmentioning
confidence: 99%
“…In literature, some surgeons have used profound hypothermia with circulatory arrest to retrieve the tumor thrombus from RA ( 11 , 12 ). The predominant limitations of this technique are its associated morbidities, including neurologic complications (delirium, psychosis, and stroke) ( 13 , 14 ), thrombocytopenia, and platelet dysfunction, resulting in significant bleeding, prolonged and/or improper rewarming with postoperative hypothermia, and overall higher mortality ( 13 , 15 ). Our approach in level IV thrombus ( Figure 5 ) was beating heart on simplified CPB without cross-clamp on aorta.…”
Section: Discussionmentioning
confidence: 99%
“…By this P‐SCP method, SCP time became longer by about 1 hour than with C‐SCP. If the CA time becomes longer than 40 to 60 minutes, the incidence of the cerebral complication increases 1,2 . Okita et al 4 reported that a retrograde cerebral perfusion (RCP) period of up to 80 minutes under a nasopharyngeal temperature of 18°C is safe.…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of cerebral complications is important for improving the surgical results of arch aneurysms. The incidence of perioperative cerebral complications ranges from 3.3% to 7.0% 1–5 . It is considered that the majority of permanent neurological injuries were due to strokes resulting from embolic phenomena.…”
mentioning
confidence: 99%